2013
DOI: 10.1002/aenm.201300489
|View full text |Cite
|
Sign up to set email alerts
|

Physically Stable Polymer‐Membrane Electrolytes for Highly Efficient Solid‐State Dye‐Sensitized Solar Cells with Long‐Term Stability

Abstract: A 3D polymer‐network‐membrane (3D‐PNM) electrolyte is described for highly stable, solid‐state dye‐sensitized solar cells (DSCs) with excellent power‐conversion efficiency (PCE). The 3D‐PNM electrolyte is prepared by using one‐pot in situ cross‐linking polymerization on the surface of dye‐sensitized TiO2 particles in the presence of redox species. This method allows the direct connection of the 3D‐PNM to the surface of the TiO2 particles as well as the in situ preparation of the electrolyte gel during device a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Unfortunately, liquid electrolytes poses challenges in integration of large area modules, difficulty in implementing tandem architectures, sealing issues, possible desorption and photodegradation of the attached dyes, which lead to lower lifetimes of the performance and practical use of the cells (Park et al, 2014;Su'ait et al, 2014;Wu et al, 2008a). Alternatively, solvent-free room-temperature ionic liquids (RTILs) such as alkyl imidazolium salt, trialkyl methylsufonium salt and alkylpyridinium salt are widely used in DSSC.…”
Section: Electrolytementioning
confidence: 99%
“…Unfortunately, liquid electrolytes poses challenges in integration of large area modules, difficulty in implementing tandem architectures, sealing issues, possible desorption and photodegradation of the attached dyes, which lead to lower lifetimes of the performance and practical use of the cells (Park et al, 2014;Su'ait et al, 2014;Wu et al, 2008a). Alternatively, solvent-free room-temperature ionic liquids (RTILs) such as alkyl imidazolium salt, trialkyl methylsufonium salt and alkylpyridinium salt are widely used in DSSC.…”
Section: Electrolytementioning
confidence: 99%
“…Also, depending on the particular application, other criteria could be decisive when selecting the most appropriate technology. [13][14][15][16] Several studies have indicated that dye desorption from the TiO 2 surface is one of the primary reasons of performance degradation. 6,7 In these applications, dye-sensitized solar cells (DSSCs) are the most flexible photovoltaic technology, offering a potentially infinite choice of colours with reasonable PCE and at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…For example, differently coloured solar cells are commercially valuable for buildings, automotive applications and portable device integration. 16 Carboxylic acids are the most commonly used anchoring group to attach dye molecules to the TiO 2 surface, but they can be easily hydrolysed in presence of water or alkaline conditions, causing their desorption, thus compromising the device operation. [8][9][10][11] A typical DSSC consists of an electron-transporting layer of dye-sensitized TiO 2 nanoparticles, which are infiltrated with a redox electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The 51 gelation is achieved by using functionalized inorganic nanoparticles [28], gelling agents [29] or 52 polymeric matrices [30]. Among all, polymers are the best choice, due to their low cost, wide 53 availability, absence of phase separation phenomena over time and high sunlight-to-electricity 54 conversion efficiency [31,32]. 55 When comparing the performance of devices containing gel-polymer electrolytes to those of 56 liquid counterparts, a photocurrent decrease and photovoltage increase are usually obtained 57 [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…It has often been noticed that the increase of the molecular weight 309 of the polymer and of its quantity with respect to that of the redox mediator solution help to increase 310 the cell durability [53]. Instead, quasi-solid cells assembled with a minimum amount of a polymer 311 dissolved in the redox mediator solution have shown higher efficiencies but poor long-term stability 312 [54].…”
mentioning
confidence: 99%